2003
DOI: 10.1308/003588403321661343
|View full text |Cite
|
Sign up to set email alerts
|

Nurse endoscopy in a district general hospital

Abstract: The nurse-led endoscopy service has been successfully initiated with a high completion rate for flexible sigmoidoscopies. All significant conditions were identified with 99% sensitivity. Nurse endoscopy is a safe, useful and practical procedure in the setting of this district general hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…There were a total of 19 studies with non-physicians performing flexible sigmoidoscopy; 7 studies[5, 13, 1719, 25, 26] involving mid-levels performing 3,976 flexible sigmoidoscopies and 12 studies[4, 11, 12, 1416, 2022, 24, 27, 28] with nurses performing 14, 886 flexible sigmoidoscopies. Among mid-levels performing flexible sigmoidoscopies (N=7), the polyp detection rate was 23.7% (95% CI 22.4–25.1%).…”
Section: Resultsmentioning
confidence: 99%
“…There were a total of 19 studies with non-physicians performing flexible sigmoidoscopy; 7 studies[5, 13, 1719, 25, 26] involving mid-levels performing 3,976 flexible sigmoidoscopies and 12 studies[4, 11, 12, 1416, 2022, 24, 27, 28] with nurses performing 14, 886 flexible sigmoidoscopies. Among mid-levels performing flexible sigmoidoscopies (N=7), the polyp detection rate was 23.7% (95% CI 22.4–25.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as with any new technique, its proper implementation involves experience and a learning curve to minimize errors in interpretation. Previous studies of conventional endoscopy demonstrated variability in findings and interpretations among gastroenterologists (5)(6)(7)(8)(9), as well as between gastroenterologists and nurses (10)(11)(12)(13). Most of the differences were associated with level of experience and borderline results (8,9).…”
mentioning
confidence: 97%
“…This strategy saved time and money without compromising the quality of the examination. It is supported by a wealth of evidence in the literature that gastroenterology nurses can efficiently interpret other types of endoscopic data (10)(11)(12).…”
mentioning
confidence: 98%
“…3,4 Urology nurse practitioners have been shown to be effective in running cystoscopy lists 5,6 and nurse-led endoscopy is now utilised within many hospital trusts with guidelines produced by a working party set up by the British Society of Gastroenterologists for nurse endoscopists. 7,8 Surgical care practitioners are also used for saphenous vein harvesting in cardiothoracic surgery. 9,10 Over 1000 patients per year are referred for minor surgical procedures by general practitioners to St Mary's NHS Trust.…”
mentioning
confidence: 99%